Need Analysis on English Teaching at Mts Nurul Qolbi: Activities and Assessment - Erniyanti Nur Fatahhela Dewi; Mentari; Nindya Hasanah (JURNAL PENDIDIKAN BAHASA DAN BUDAYA, 2023)
The  research  aims  to find  out English Classroom activities and assessment based on students’ need analysis and teacher’s perception. The quantitative and qualitative method were  conducted in this research to describe the students’ needs. In collecting the data, the  researchers applied interview for teacher and  questionnaire  for  the  students  as  the instrument of the research. There were one teacher and 30 students as participants in this research by conducting purposive sampling. The findings showed that researchers can use the topic that they provide to develop materials in needs analysis for the student in language teaching. In addition, assessment activity on the topic of invitation, give instructions and ask permissian was suggested to use feedback from friends. While, making a greeting card topic was suggested to use feedback from the teacher. Hence, showing the existence of a person or thing topic was suggested to use role play.